Waveform capnography in the South African prehospital setting: knowledge assessment of qualified advanced life support (ALS) paramedics - Wylie, Craig Alexander (Division of Emergency Medicine, 2017)
Although there is extensive literature regarding out-of-hospital use of capnography, the willingness and knowledge of South African paramedics where capnography is available for routine use is poorly understood. From informal reviews, it would appear that even when capnography is available the practitioners decided to not use the tool. Aim: To determine the knowledge of prehospital providers with respect to the use of capnography to guide decision making in the treatment of patients. Methods: A cross-sectional research-generated survey of 80 out-of-hospital advanced life support paramedic providers in South Africa working in the private industry where capnography is available. Participants will be recruited with the assistance of the company's research committee using an email platform, and consent process. The questionnaire will establish the knowledge, ability and willingness of advanced life support paramedics to identify and use capnography as part of their clinical decision making process. Descriptive statistics will be used to interpret and report the data. The study should be concluded within 6 months of receiving ethical approval from Human Research Ethics Committee of the University of Cape Town. Discussion: The findings of the study will describe a cohort of out-of-hospital practitioners' knowledge and willingness to use capnography in an environment where it is routinely available. Recommendations will be made regarding the need for further policy development and change management for the implementation of best practice.